The Effect of Current Ratio, Total Asset Turnover and Time Interest Earned on Return On Assets in Transportation and Logistics Sub-Sector Companies Registered at the Bei Period 2019-2021 - Ifa Mustaghfiroh; Wahyudiono (Journal of World Conference (JWC), 2023)
This study aims to analyze the effect of Current Ratio, Total Asset Turnover and Time Interest Earned on Return On Assets in transportation and logistics sub-sector companies listed on the Indonesia Stock Exchange. The objects of this research are 10 companies engaged in transportation and logistics that are listed on the Indonesian Stock Exchange. This study uses secondary data, financial reports published by transportation and logistics sub-sector companies listed on the Indonesia Stock Exchange in the period 2019 - 2021. The variables studied are Current Ratio, Total Asset Turnover, Time Interest Earned and Return On Assets. The analysis technique uses multiple regression analysis with SPSS 18. The results of the study are partial Current Ratio, Total Asset Turnover and Time Interest Earned have a significant positive effect on Return On Assets. While simultaneously the Current ratio, Total Asset Turnover and Time Interest Earned together have a positive and significant effect on Return On Assets.